Moving Forward in Cervical Cancer: Enhancing Susceptibility to DNA Repair Inhibition and Damage, an NCI Clinical Trials Planning Meeting Report. (27th March 2020) - Harkenrider, Matthew M; Markham, Merry Jennifer; Dizon, Don S; Jhingran, Anuja; Salani, Ritu; Serour, Ramy K; Lynn, Jean; Kohn, Elise C
Abstract: Cervical cancer is the fourth most common cancer in women worldwide, and prognosis is poor for those who experience recurrence or develop metastatic disease, in part due to the lack of active therapeutic directions. The National Cancer Institute convened a Cervical Cancer Clinical Trials Planning Meeting in October 2018 to facilitate the design of hypothesis-driven clinical trials focusing on locally advanced, metastatic, and recurrent cervical cancer around the theme of enhancing susceptibility to DNA repair inhibition and DNA damage. Before the meeting, a group of experts in the field summarized available preclinical and clinical data to identify potentially active inducers and inhibitors of DNA. The goals of the Clinical Trials Planning Meeting focused on identification of novel experimental strategies capitalizing on DNA damage and repair (DDR) regulators and cell cycle aberrations, optimization of radiotherapy as a DDR agent, and design of clinical trials incorporating DDR regulation into the primary and recurrent or metastatic therapies for cervical carcinoma. Meeting deliverables were novel clinical trial concepts to move into the National Clinical Trials Network. This report provides an overview for the rationale of this meeting and the state of the science related to DDR regulation in cervical cancer.